Polluted River Water Treatment Via Membrane Photocatalytic Reactor (MPR) Incorporated ZnO-Kaolin - Rais Hanizam Madon; Wan Haikal Fitri Wan Ahmad Rizalle; Siti Nurfatin Nadhirah Mohd Makhtar; Mohamad Alif Hakimi Hamdan; Nor Afzanizam Samiran; M. Zahar Abd. Jalal; Muhamad Khairul Ilman Sarwani; Malvina Ludan (Journal of Advanced Mechanical Engineering Applications, 2024)
Rivers provide essential resources for human use both in agriculture and aquatic ecosystems, which are particularly vulnerable to contamination. The polluted river water was treated using MPR incorporated Zno-Kaolin. The ZnO-Kaolin was synthesized through precipitation method and calcined at 550C. The characterization of the ZnO-kaolin was done using FTIR and XRD. It was found no impurities occurred during the synthesis. The Zno-Kaolin was then incorporated with MPR to investigate the reduction performance under different conditions, i) effect of initial pH, ii) effect of dosing and iii) effect of initial concentration. it was found that the optimal pH for the reduction is at pH 5, and at dosage 0.05 g/L. It was found the 100% concentration gave the highest reduction for all water quality index (salinity,TDS, conductivity). It can be concluded that MPR incorporated Zno-kaolin effectively treat polluted river water.